2013
DOI: 10.1128/mcb.00887-12
|View full text |Cite
|
Sign up to set email alerts
|

A-Kinase-Anchoring Protein–Lbc Anchors IκB Kinase β To Support Interleukin-6-Mediated Cardiomyocyte Hypertrophy

Abstract: bIn response to stress, the heart undergoes a pathological remodeling process associated with hypertrophy and the reexpression of a fetal gene program that ultimately causes cardiac dysfunction and heart failure. In this study, we show that A-kinase-anchoring protein (AKAP)-Lbc and the inhibitor of NF-B kinase subunit ␤ (IKK␤) form a transduction complex in cardiomyocytes that controls the production of proinflammatory cytokines mediating cardiomyocyte hypertrophy. In particular, we can show that activation of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
24
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 29 publications
(24 citation statements)
references
References 40 publications
(49 reference statements)
0
24
0
Order By: Relevance
“…CAMP and its effectors are under tight spatiotemporal control by a family of scaffolding proteins with over 50 members called A-kinaseanchoring proteins (AKAPs) (32,37,38). AKAPs regulate diverse cellular processes, including release of inflammatory cytokines from cardiomyocytes and alveolar macrophages (8,21). For example, in alveolar macrophages, AKAP10 is required for the potentiation of LPS-induced IL-6 and IL-10 production by the cAMP-elevating agonist prostaglandin E 2 (PGE 2 ) (21).…”
mentioning
confidence: 99%
“…CAMP and its effectors are under tight spatiotemporal control by a family of scaffolding proteins with over 50 members called A-kinaseanchoring proteins (AKAPs) (32,37,38). AKAPs regulate diverse cellular processes, including release of inflammatory cytokines from cardiomyocytes and alveolar macrophages (8,21). For example, in alveolar macrophages, AKAP10 is required for the potentiation of LPS-induced IL-6 and IL-10 production by the cAMP-elevating agonist prostaglandin E 2 (PGE 2 ) (21).…”
mentioning
confidence: 99%
“…During the last few years, several studies using primary cultures of rat NVMs as a model system have shown that AKAPs organize signaling complexes that regulate hypertrophic signaling pathways (9)(10)(11)(12)(23)(24)(25)(26)(27). While these findings contributed importantly to our understanding of how this family of scaffolding proteins coordinates hypertrophic signals at the cellular level, it remains to be established whether AKAP-based signaling complexes can control cardiac hypertrophy in vivo.…”
Section: Discussionmentioning
confidence: 99%
“…Previous work has identified an anchoring protein expressed in cardiomyocytes, termed AKAP-Lbc, which acts as a RhoA selective guanine nucleotide exchange factor (GEF) (8) and serves as a scaffold for multiple signaling enzymes regulating cardiomyocyte growth (9)(10)(11)(12). Silencing of AKAP-Lbc expression in rat NVMs strongly reduces RhoA activation and hypertrophic responses induced by GPCR agonists (9,10), suggesting a link between AKAPLbc-mediated RhoA activation and cardiomyocyte hypertrophy.…”
mentioning
confidence: 99%
“…More-detailed biochemical mapping experiments identified a short helical region at the end of the AKAP-Lbc pleckstrin homology (PH) domain that was responsible for interaction with IKK␤. Furthermore, a point mutation in AKAP-Lbc, W2328L, dramatically reduces IKK␤ binding (7). Next, del Vescovo et al showed that short hairpin RNA (shRNA)-mediated silencing of AKAPLbc impairs activation of an NF-B reporter gene.…”
mentioning
confidence: 99%
“…In this issue, del Vescovo et al describe an intriguing new connection between adrenergic, small GTPase, and cytokine signaling that regulates stress effects on cardiac remodeling (7). del Vescovo and colleagues have identified a robust protein-protein interaction between A-kinase-anchoring protein (AKAP)-Lbc and IB kinase ␤ (IKK␤), a crucial regulator of NF-B signaling.…”
mentioning
confidence: 99%